Security trumps drug control: How securitization explains drug policy paradoxes in Thailand and Vietnam. (3rd July 2016) - Windle, James
Abstract: This paper investigates the paradoxes inherent in Thai and Vietnamese drug policies. The two countries have much in common. Both are ultra-prohibitionist states which employ repressive policies to contain drug markets. Their policies have, however, diverged in two key areas: opium suppression and harm reduction. Thailand implemented an effective intervention to suppress opium farming centred upon alternative development, whereas Vietnam suppressed opium production through coercive negotiation with nominal alternative development. Vietnam has embraced elements of harm reduction, whereas Thailand has been slow to implement harm reduction policies. This paper hypothesises that these two differences are largely a product of their perceived relationship to security. The two cases demonstrate how once an issue is securitized the ultra-prohibitionist rules of the game can be broken to allow for more humane and pragmatic policies.